POLITIK HUKUM LINGKUNGAN HIDUP DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Dani Amran Hakim (Universitas Lampung, 2015)
The legal political environment in Indonesia in terms of protection, management and control of environmental pollution in Indonesia and to investigate the implementation of environmental pollution control and law enforcement in Indonesia. the results of the study stated that the renewal law of Environmental management is influenced by a variety of development changes occurring in society, such as the influence of the era of democratization, industrialization, advancement of science and technology and the rise of the welfare demands of various parties. Political aspects contained in the politics of Law Number 32 of 2009 on the protection and management of the environment has not been run in accordance with the legal political objective, because there are natural resources that can not be utilized for the prosperity and welfare of the people. It is also still a lot of water pollution, air pollution, deforestation and other actions of the parties who damage the environment. It is necessary to implement environmental management to preserve the environment and develop skills which are harmonious, consistent and balanced in order to support the implementation of the development of environmentally sustainable. Law enforcement agencies in understanding the perceived environmental legal system are still experiencing difficulties. Lack of understanding of the law enforcement officers will cause rules is formed in one unified national legal system will deviate from the direction of the political objectives of the law. The need for clear law enforcement for the doer / destroyer of the environment in order to create a deterrent effect and between 3 penalties (criminal, civil and administrative) is not overlapping. Law enforcement difficult because of the difficulty of proving and determining the standard criteria of environmental damage. Keywords: Legal Politic, Environment, The Act Number 32 years 2009 on The Protection and Environmental Management